Family environment and childhood sexual victimization - A test of the buffering hypothesis - Ray, K. C. (Journal of interpersonal violence, 1997)
The potential of family cohesion and organization to act as buffers against the long-term, negative impact of childhood sexual abuse was examined. College women (N = 266), including 141 who had experienced childhood sexual abuse, completed self-report measures of current depressive symptomatology, self-esteem, and social adjustment. Family cohesion and organization were measured by the Family Environment Scale. Although no evidence for a buffering effect was indicated, multiple regression analyses revealed that both family characteristics were significantly related to participants' current social and psychological adjustment